Respon pertumbuhan dan hasil tanaman selada romaine (Lactuca sativa L. var. Longifolia) terhadap pemberian berbagai dosis pupuk bekas budidaya maggot (kasgot) - Ahmad Taofik; Astiana Rizky; Liberty Chaidir (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
The romaine lettuce plant is a plant whose production continues to increase so that the demand for romaine lettuce in Indonesia is not sufficient due to inefficient cultivation. This means that romaine lettuce plants have to be imported to meet the needs of the community but do not meet market needs. Providing cassava fertilizer from household waste feed is one effort to meet the nutritional needs of romaine lettuce, so that production can increase. This research aims to determine the effect of different doses of cassava fertilizer on the growth and yield of romaine lettuce plants (Lactuca sativa L. var longifolia.). This research was carried out from February to July 2024 at the Land Balai Pengembangan dan Produksi Benih Perkebunan (BPPBP) and at Labolatorium Teknologi Benih Universitas Sunan Gunung Djati Bandung. This research used a Randomized Group Design (RAK) consisting of 6 treatments and 4 replications. Each experimental unit contained 3 plant samples, so that 72 plant samples were obtained (A= Control (soil); B= Kasgot organic fertilizer 9 t ha-1; B= Kasgot organic fertilizer 10 t ha-1; C= Kasgot organic fertilizer 11 t ha-1; D= Kasgot organic fertilizer 12 t ha-1; F= NPK 16:16:16). The results of the study showed that the use of cashew fertilizer with household waste feed had an effect on the growth and yield of romaine lettuce plants with an effective dose of 10 t ha-1.